Histopathologic Findings of Coronavirus in Lung: A Mini-Review - Bita Geramizadeh; Mahsa Marzban (SAGE Publishing, 2020)
Coronaviruses (CoVs) are important human and animal pathogens. There have been several outbreaks of lung involvement by this category of viruses in the world, ie, severe acute respiratory syndrome (SARS-CoV-1) in 2002 and 2003, the Middle East respiratory syndrome (MERS-CoV) in 2012, and the new coronavirus (2019-nCoV) outbreak of pneumonia from Wuhan, China, since December 2019. There have been several studies about the clinical features and imaging features, but very few reports have been published about pathologic findings in lung tissue, which was partly because of the lack of tissue diagnosis secondary to suddenness of the outbreak. Overall, less than 30 reports have been published in the literature about histologic findings of lung in these viruses, so far. In this report, we will review the published reports about the histopathologic findings of lung tissue in the patients infected with SARS-CoV-2 in comparison with 2 other coronaviruses that have caused outbreaks, ie, SARS-CoV-1 and MERS-CoV.